Komunikacijski ali sporočanjski frazemi - Stramljič Breznik, Irena (Jezik in slovstvo, 2001)
Pragmatic phrasemes are those whose meaning is not (only) denotative, but it determined by the circumstances of the communicative act. The paper discusses a group of communicative phraseologic patterns with sentential structure from the material of the Dictionary of the Standard Slovene Literary Language. They are classified into four groups according to the speaker's relationship to the addressee, the theme, the medium of communication, and other circumstances in a communicative act.
Keywords: frazemi; Slovene; slovenščina; frazeologija; phraseology